Project-Based Blended Learning Model: Innovative Solution to Improve Stiudents’ Scientific Article Writing Skills - Djaffar Lessy; Dinar Riaddin; Qurrota A'yun (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Scientific writing skills are essential for students in higher education, particularly in preparing them to contribute to academic publications. However, many students still face difficulties in composing scientific articles that meet academic standards. This study aims to develop a Project-based Blended Learning (PjB2L) model to improve the ability of IAIN Ambon students to write scientific articles. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants were 24 students from Mathematics Education, PGMI, and MPI study programs who had previously conducted research. Data were collected through a media validity questionnaire, a scientific article writing ability test, and a scientific article writing rubric. The results indicate that the developed PjB2L model is both valid and effective in enhancing students’ scientific writing skills, as evidenced by a significant increase in pretest and posttest scores after the learning intervention. In conclusion, the PjB2L model serves as a viable alternative learning approach that leverages information and communication technology (ICT) to facilitate both independent and collaborative learning in scientific writing.